ANALISA SISTEM INFORMASI KEPENDUDUKAN PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL - Helda Yunita; Sri Melati; Lifiya Lifiya (Pusat Riset dan Inovasi Nasional, 2021)
The recording and processing of population data is the responsibility of the district/city government, where the implementation begins with the sub-district as the spearhead of population registration. These services need to be done quickly and precisely to get information. But in reality, data processing at the Department of Population and Civil Registry is still done in the form of books or archives, so errors often occur and even data archives are lost or damaged because there are too many records. Therefore, a web-based information system is researched and analyzed which is expected to be able to dynamically store population data and be able to process and create population reports anytime and anywhere without having to take a long time and effort. The result of the research is the success of creating a website that functions as a Population Information System at the Department of Population and Civil Registry, with this website it will be able to assist in managing population data and make it easier to search data and also make population reports. Making a Population Information System at the Population and Civil Registry Office is web-based and is made using the PHP and MySQL programming languages so that the system can be accessed anywhere and anytime.